Delayed lupus nephritis (2008)
Objective: To describe and analyse the clinical and immunological characteristics of a large series of patients with delayed lupus nephritis (LN). Methods: A cross-sectional study was carried out. Patients with systemic lupus erythematosus (SLE) who developed renal involvement ?5 years after the first manifestation (s) of the disease (delayed LN, n = 48) were compared with patients with SLE in whom LN developed within 5 years or less after SLE appeared (early-onset LN, n = 187). A control group, the no LN (NLN) group, comprised patients with longstanding SLE (duration of disease >10 years) who had never shown signs of renal involvement (n = 164). Results: The group with delayed LN was positively associated with Sjögren's syndrome, lung involvement and antiphospholipid syndrome as compared with early LN. However, its renal clinical expression and histopathological patterns were similar to those of early-onset LN. The frequency of anti-dsDNA, anti-Sm and anti-RNP antibodies was higher in patients with LN than in the NLN group, as was the frequency of low complement levels. Jaccoud's arthropathy was a protective factor for nephritis. Conclusions: Delayed LN is not uncommon in patients with SLE. The identified risk factors might aid in its diagnosis and enhance the ability to identify patients at risk for this complication of SLE.